Characterization and PAH removal performance of microbe-immobilized biochars derived from different feedstocks - Sun, Anqi; Liang, Jiaqing; Zhou, Haixuan; Coulon, Frederic; Hou, Yanwei; Cai, Chao (Elsevier, 2026)
Microbial degradation is the primary mechanism for purifying polycyclic aromatic hydrocarbon (PAH) contamination in environments, and biochar immobilization is an effective technology to enhance biodegradation, but the process parameters of the immobilization technology still require further systematic evaluation. Here, biochars derived from pig manure (PM), bamboo (BB), rice straw (RS), and soybean straw (SS) were used as carriers of Mycobacterium sp. ZL7, and the optimal biochar dosage of 1:30 (w/v) and immobilization time of 24 h were determined. The immobilization effects followed the order of RS > SS > PM > BB. Scanning electron microscopy and physicochemical properties revealed that porous structures acted as shelters for bacteria, and high nitrogen content, large pore size and high-water holding capacity played important driving roles in immobilization. In the single-substrate system, pyrene removal rates of the PM-, RS- and SS-immobilized materials were greater than 96 %, which were significantly higher than those of the biochar alone or the free strains. An orthogonal design experiment in historically PAH-contaminated soil further revealed that, compared with free strain, immobilized materials combined with high moisture content and moderate salicylic acid or Brij 30 can effectively increase the abundance of bacteria and the nidA gene, and enhance the dehydrogenase and polyphenol oxidase activities. The removal rate of total PAHs increased by 8.53 %-30.45 % after 24 d. Moreover, biochar with strong immobilization capacity showed better PAH removal effects. This study provides a scientific basis and practical reference for biochar-immobilized microorganisms to enhance the self-purification of PAH-contaminated soil.
Keywords: 4105 Pollution and Contamination; Environmental Sciences; 34 Chemical sciences; 37 Earth sciences; Polycyclic aromatic hydrocarbons (PAHs); Self-purifying; Microorganism; Biochars; Immobilization